Exposure to Virtual Social Stimuli Modulates Subjective Pain Reports. (2014) - Vigil, Jacob M; Torres, Daniel; Wolff, Alexander; Hughes, Katy
Abstract : BACKGROUND: Contextual factors, including the gender of researchers, influence experimental and patient pain reports. It is currently not known how social stimuli influence pain percepts, nor which types of sensory modalities of communication, such as auditory, visual or olfactory cues associated with person perception and gender processing, produce these effects. OBJECTIVES: To determine whether exposure to two forms of social stimuli (audio and visual) from a virtual male or female stranger modulates cold pressor task (CPT) pain reports. METHODS: Participants with similar demographic characteristics conducted a CPT in solitude, without the physical presence of an experimenter or another person. During the CPT, participants were exposed to the voice and image of a virtual male or female stranger. The voices had analogous vocal prosody, provided no semantic information (spoken in a foreign language) and differed only in pitch; the images depicted a middle-age male or female health care practitioner. RESULTS: Male participants, but not females, showed higher CPT pain intensity when they were exposed to the female stimuli compared with the male stimuli. Follow-up analyses showed that the association between the social stimuli and variability in pain sensitivity was not moderated by individual differences in subjective (eg, self-image) or objective measurements of one's physical stature. DISCUSSION: The findings show that exposure to virtual, gender-based auditory and visual social stimuli influences exogenous pain sensitivity. CONCLUSION: Further research on how contextual factors, such as the vocal properties of health care examiners and exposure to background voices, may influence momentary pain perception is necessary for creating more standardized methods for measuring patient pain reports in clinical settings.